Analisis Skala Produksi Usahatani Jagung Pipil - Nanda Rosyita; M. Nasir Ismail; Khumaira Khumaira (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Corn (Zea mays, Linn) is an industrial raw material and animal feed, Corn is classified as a strategic commodity because it meets the criteria, among others, has an influence on the price of other food commodities and has bright prospects. The increasing demand for maize in the country is closely related to the development of the food and feed industry. Therefore, efforts to increase maize production need to receive greater attention. Increased production can also still be pursued through improved harvest and post-harvest handling. The purpose of the study was to determine how much income and scale of production (returns to scale) on pipil corn farming in Teuladan Village, Seulawah Valley District, Aceh Besar Regency. The research method is the